Investigation of Naturally Occurring Single-Nucleotide Variants in Human TAAR1 - Mühlhaus, Jessica; Dinter, Juliane; Jyrch, Sabine; Teumer, Alexander; Jacobi, Simon F.; Homuth, Georg; Kühnen, Peter; Wiegand, Susanna; Grüters, Annette; Völzke, Henry; Raile, Klemens; Kleinau, Gunnar; et al. (Frontiers in Pharmacology, 2017)
Activation of trace amine-associated receptor 1 (TAAR1) in endocrine pancreas is involved in weight regulation and glucose homeostasis. The purpose of this study was the identification and characterization of potential TAAR1 variants in patients with overweight/obesity and disturbed glucose homeostasis. Screening for TAAR1 variants was performed in 314 obese or overweight patients with impaired insulin secretion. The detected variants were functionally characterized concerning to TAAR1 cell surface expression and signaling properties and their allele frequencies were determined in the population-based Study of Health in Pomerania (SHIP). Three heterozygous carriers of the single nucleotide missense variants p.Arg23Cys (R23C, rs8192618), p.Ser49Leu (S49L, rs140960896), and p.Ille171Leu (I171L, rs20079534) were detected in the patient cohort. While S49L and I171L were found in obese/overweight patients with slightly impaired glucose homeostasis, R23C was identified in a patient with complete-loss-of insulin production. Functional in vitro characterization revealed a partial loss-of-function for S49L and a complete loss-of-function for R23C. The frequency of the R23C mutation in 2018 non-diabetic control individuals aged 60 years and older in the general population-based SHIP cohort was lower than in the analyzed patient sample. Both variants are rare in the general population indicating a recent origin in the general gene pool and/ or the consequence of pronounced purifying selection, in line with the obvious detrimental effect of the mutations. In conclusion, our study provides hints for the existence of naturally-occurring TAAR1 variants with potential relevance for weight regulation and glucose homeostasis.